Cultural studies and intersectionality in English language education: exploring students' engagement in issues of celebrity, identity, gender and sexuality. Issue 6 (2nd November 2021) - Svarstad, Lone Krogsgaard
ABSTRACT: The increasing orientation towards interculturality in language education calls for research to investigate teacher and student perceptions and practices of interculturality. Most research already conducted in this area primarily concerns teacher perceptions and practices, but this study contributes to an exploration of how lower secondary school students (15-year-olds) engaged in broader issues of interculturality, which include issues of celebrity, identity, gender and sexuality. The participatory action research intervention analysed in this paper explored the pedagogical potential of Cultural studies and the case of celebrity Miley Cyrus' toying with intersecting identities. The study's findings show that many of the participating students had sufficient linguistic and analytical resources to engage in a discourse analysis of an open letter to Miley Cyrus on Facebook from Sinead O'Connor. From the study's explorative intervention, it emerged that knowledge about Cultural studies with focus on three key concepts, intersectionality and othering (Dervin, F. 2016. Interculturality in Education: A Theoretical and Methodological Toolbox . London: Palgrave Macmillan) and subtextuality (Svarstad, L.K. 2016. Teaching interculturality: developing and engaging in pluralistic discourses in English Language Teaching, Århus University Press) supported the analysis of classroom dialogues and helped to conceptualise and develop a metalanguage of broader issues of interculturality.